Symbols of Prehistoric Mesopotamia - Goff, Beatrice Laura (1963)
1. The Hassunah Period; 2. The Halaf Period; 3. The Ubaid Period; 4. The Role of Abstract Art in Early Mesopotamia; 5. The Uruk Period; 6. The Jemdet Nasr Period; 7. The Gawra Period; 8. The Ninevite Period; 9. The Role of Amulets in Mesopotamian Ritual Texts; 10. The Origin of Sumerian Mythology.